2007
DOI: 10.1111/j.1600-0501.2007.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histomorphometry and resonance frequency analysis of implants with moderately rough surfaces in a loaded animal model

Abstract: In conclusion, the benefit of rough surfaces relative to minimally rough ones in this loaded animal model was confirmed histologically. The comparison of different surface treatment modalities revealed no significant differences between the modern moderately rough surfaces. Resonance frequency analysis seems to be influenced in a major part by the transducer used, thus prohibiting the comparison of different implant systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…(31) found no correlation between bone-implant contact (BIC) and RFA, while Al-Nawas et al (32) confirmed the benefits of a rough implant surface for increased RFA-measured stability. Karl et al (33) compared the different locations of mandibular and maxillary ITI implants and found a significant correlation between these variables.…”
Section: Resultsmentioning
confidence: 99%
“…(31) found no correlation between bone-implant contact (BIC) and RFA, while Al-Nawas et al (32) confirmed the benefits of a rough implant surface for increased RFA-measured stability. Karl et al (33) compared the different locations of mandibular and maxillary ITI implants and found a significant correlation between these variables.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the mentioned parameters of the primary and secondary stability, the implant surface osteoconductive characteristics are factors which affect the implant bone response and quality of the bone implant interface [7,8]. Surface treatment helps to enhance secondary stability after insertion by promoting osseointegration [6,9,10]. Various methods have been developed and tested in order to coat metal implants, e.g., plasma spraying, sputter deposition, sol-gel coating, electrophoretic deposition or biomimetic precipitation [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…During the osseointegration period, bone gradually remodels to the implant threads and thus the secondary stability is attained by direct bone to implant contact [5]. It is proportioned with implant success rate, depending on bone remodelling induced by a mechanical stress situation during the initial phase of bone healing and surface modification of the implants [6]. According to current literature, there are discussions concerning the ability of implants to withstand early or immediate loading in order to reduce waiting time for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, experimental studies comparing different types of surface and geometry of implants has been performed [6,[10][11][12][13]. However, few studies have compared the implants with hydrophilic sandblasted and acid etched surface with anodic oxidation surface in the early stages of bone repair [11].…”
Section: Discussionmentioning
confidence: 99%
“…The orientation of collagen fibers is strictly dependent on the shape of the implants [10]. Experimental studies have compared different types of implant surfaces and geometries [11][12][13]. However, few studies have compared chemically treated sandblast and acid etched, which is hydrophilic (modified), with anodic oxidized surface [11].…”
Section: Introductionmentioning
confidence: 99%